Religious freedom and discrimination - Healey, Justin (Thirroul, NSW : Spinney Press, 2015)
Annotation. According to the latest census, 68.3% of Australians identified a religious affiliation, while an unprecedented 22% declared themselves to be of "no religion". Religious freedom is a fundamental human right, safe-guarded by the Australian Constitution; individuals are free to express a diversity of views, as long as they do not incite religious hatred. This book provides an overview of the latest trends in religious affiliation in Australia. The book also explores human rights and religion in Australian law, in response to recent calls for stronger legislative recognition and protection of religious freedoms, including exemptions from anti-discrimination laws. How much vilification is experienced by religious groups in Australia? Should faith-based organisations be allowed to discriminate to 'avoid injury to religious sensitivities'? Is there enough separation between religion and the state, or should Australia's government be more secular? Religious freedom is a complex and contested concept - where does the balance lie?
Includes bibliographical references and index.
Keywords: Freedom of religion -- Australia; Religious tolerance -- Australia; Human rights -- Australia; Religion and state -- Australia; POLITICAL SCIENCE / Political Freedom & Security / Civil Rights; POLITICAL SCIENCE / Political Freedom & Security / Human Rights; Electronic books